1997
DOI: 10.1046/j.1365-2648.1997.1997025273.x
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of the ‘waiting game’: a critical examination of the psychosocial issues in diagnosing breast cancer

Abstract: Undergoing diagnostic investigations for symptoms of breast disease constitutes an intensely stressful experience for any woman. The widespread use of contemporary fine-needle techniques throughout specialist breast clinics, whilst removing the necessity of hospitalization and general anaesthesia for many women, has introduced the notion of the 'waiting game'. The ability to ascertain definitive results within a matter of hours has led to diversification in the structure of diagnostic breast services; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Several studies have shown that the period surrounding the diagnosis of breast cancer is one of the most stressful times for women and their partners [23][24][25][26][27]. In our series, 51% of the final histological diagnoses were benign and 49% were malignant.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have shown that the period surrounding the diagnosis of breast cancer is one of the most stressful times for women and their partners [23][24][25][26][27]. In our series, 51% of the final histological diagnoses were benign and 49% were malignant.…”
Section: Discussionmentioning
confidence: 62%
“…Patients presenting for transrectal ultrasound (TRUS)-guided needle biopsy typically have substantial levels of presurgical emotional distress, which has been shown to predict pain [3][4][5]. Although modern drug regimens are effective in eliminating pain and improving tolerability of minor surgical procedures, surgery continues to be associated with clinically significant side effects, including postsurgical pain, nausea, and fatigue [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One possible predictor of expectancies for post-surgical pain and fatigue is pre-surgical distress, often experienced by women awaiting curative as well as diagnostic breast surgery (e.g., Benedict, Williams, & Baron, 1994;Deane & Degner, 1998;Poole, 1997). According to Leventhal's dual process model (Leventhal, Leventhal, & Cameron, 2001), emotional factors can affect cognitive factors.…”
Section: Introductionmentioning
confidence: 99%